Colonization with antibiotic resistant bacteria in communities and hospitals across six countries, including Bangladesh, Botswana, Chile, Guatemala, India, and Kenya - Gemma Parra; Ebbing Lautenbach; Mosepele Mosepele; Naledi Mannathoko; Robert Gross; Douglas R. Call; Brooke M. Ramay; Sylvia Omulo; C. P. Girish Kumar; Tarun Bhatnagar; Fahmida Chowdhury; Syeda Mah-E-Muneer; et al. (Scientific Reports)
Abstract The recognized burden of antimicrobial resistance (AR) is greatest in low- and middle-income countries (LMICs), but limitations in surveillance preclude accurate estimates of AR. We aimed to evaluate colonization in communities and hospitals across six LMICs for two clinically-important pathogens: extended-spectrum cephalosporin-resistant Enterobacterales (ESCrE) and carbapenem-resistant Enterobacterales (CRE). Participants in hospitals and communities provided rectal swabs or stool samples for ESCrE and CRE identification. Isolates recovered from selective agars underwent confirmatory identification and antibiotic susceptibility testing (AST) using Vitek® 2, MALDI-TOF, and/or disc diffusion testing. ESCrE and CRE were defined based on established breakpoints of phenotypic resistance to third-generation cephalosporins and carbapenems, respectively, to calculate prevalence of colonization. Community prevalence estimates were weighted to account for sampling design differences. A total of 10,139 participants across the 6 countries provided samples; 63% were females with a median age of 35 years (range: 0–99). Colonization with ESCrE in hospitals was high in all sites (range 34–84%). In communities, ESCrE colonization ranged from 22 to 77%. Prevalence of CRE colonization in hospitals ranged from 7 to 36% and in communities ranged from < 1 to 14%. These findings reveal a high burden of AR colonization in LMICs in both communities and hospitals. Cost-effective strategies to reduce AR colonization burden are needed in LMICs.